Unique Reciprocal Association Seen Between Latent Tuberculosis Infection and Diabetes Is Due to Immunoendocrine Modulation (DM-LTB-1) - Aravindhan, Vivekanandhan; Bobhate, Anup; Sathishkumar, Kuppan; Patil, Aruna; Kumpatla, Satyavani; Viswanathan, Vijay (Frontiers in Microbiology, 2022)
Aim: The prevalence of latent tuberculosis infection (LTBI) among diabetes patients is poorly studied. In, the present study the prevalence of LTBI among pre-diabetes and diabetes patients was studied, along with immunoendrocrine biomarkers (n=804). Methods: LTBI was screened by Quantiferon TB gold in Normal glucose tolerance ((NGT); n = 170), Pre-diabetes (PDM; n = 209), Newly diagnosed diabetes (NDM; n = 165) and Known diabetes (KDM; n = 260) subjects. CRP, TNF-α, IL-6, IL-1β, IFN-β, IL-12, IFN-γ, IL-2, insulin, leptin and adiponectin levels in serum and IFN-γ levels in quantiferon supernatants was quantified by ELISA. The expression of T-bet was quantified using qRT-PCR. Serum TBARS and nitrite levels were quantified by colourimetry. Results: The LTBI prevalence was 32% in NGT, 23% in PDM, 24% in NDM and 32% in KDM groups, with an adjusted OR of 0.61 (p<0.05). Downregulation of CRP, TNF-α and nitrites and upregulation of adiponectin could be responsible for LTBI mediated protection against insulin resistance (IR), while the high levels of IL-1β, IL-12 and leptin could be responsible for IR mediated anti-TB immunity. The defective antigen specific IFN-γ response, as seen in the KDM group, could be responsible for low detection rate of LTBI and high probability of endogenous reactivation. Conclusion: There appears to be a biphasic relationship between diabetes-latent tuberculosis: At early stages of diabetes it is reciprocal; while at a late stage it is synergistic - this important phenomenon obviously needs further research.